Macrolepiota capelariae (Agaricaceae, Basidiomycota): a new species from the Brazilian Atlantic Rainforest with extended records to Argentina and Mexico - Souza, Adriana D.; Nascimento, Cristiano C. Do; Freitas, Daline S.; Menolli Jr., Nelson (Phytotaxa, 2022)
A new Macrolepiota species from Brazil, M. capelariae, is proposed here based on morphological and molecular evidence. The description and illustrations are based on specimens collected in a remnant of the Atlantic Rainforest in São Paulo, Southeast Brazil. Analyses of nrITS sequences supported the recognition of this new species, in combination with morphological evidence, and revealed its phylogenetic placement in Macrolepiota sect. Macrolepiota. Macrolepiota capelariae is characterized by its medium to large and very tall basidiomata, light brown to pale greyish brown, brownish orange or clay brown pileus surface, ellipsoid to oblong, dextrinoid basidiospores with a distinct germ pore, narrowly clavate to sometimes clavate cheilocystidia, a trichodermal pileus covering composed of mostly clavate to narrowly clavate, thick-walled terminal elements, and absence of clamp connections. Nomenclatural types are deposited at the herbarium SP from the ‘Instituto de Pesquisas Ambientais’, São Paulo, Brazil. A comparison with allied species is provided. An earlier varietal name proposed based on a Brazilian material, viz. Lepiota procera var. vulpina Rick, could corresponds to a synonym of the new taxa, but the lack of nomenclatural type, extant original herbarium specimens, and the record of confident distinctive characters for this variety prevent a reliable correlation with the new species proposed.